Answer:
Four
Step-by-step explanation:
Let's expand and see how many nonzero terms:
⇒ (x+4)(2x²+3x+9)-3(x³-2x²+7x)=
⇒ 2x³ + 3x² + 9x + 8x² + 12 + 36 - 3x³ + 6 x² - 21 x=
⇒ - x³ + 17x² - 12x + 12
As we see the expression has four nonzero terms
<u>answers for the blank:</u> 23 and 25
<u>explanation:</u> plug in the n to the equation and solve! :)
hope this helps ❤ from peachimin
Ok, ranked by axis of symmetry
basically x=something is the axis of symmetry
the way to find the axis of symmetry is to convert to vertex form and find h and that's the axis of symmetry
but there's an easier way
for f(x)=ax^2+bx+c
the axis of symmetry is x=-b/2a
nice hack my teacher taught me
so
f(x)=3x^2+0x+0
axis of symmetry is -0/(3*2), so x=0 is the axis of symmetry for f(x)
g(x)=1x^2-4x+5,
axis of symmetry is -(-4)/(2*1)=4/2=2, x=2 is axis of symmetry for g(x)
h(x)=-2x^2+4x+1
axis of symmetry is -4/(2*-2)=-4/-4=1, x=1 is the axis of symmetry for h(x)
0<1<2
axisies
f(x)<h(x)<g(x)
order based on their axises of symmetry is f(x), h(x), g(x)